2014
DOI: 10.1002/cphc.201402643
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Circular Dichroism of Bicyclic Ketones from Multiphoton Ionization with Femtosecond Laser Pulses

Abstract: Photoelectron circular dichroism (PECD) is a CD effect up to the ten-percent regime and shows contributions from higher-order Legendre polynomials when multiphoton ionization is compared to single-photon ionization. We give a full account of our experimental methodology for measuring the multiphoton PECD and derive quantitative measures that we apply on camphor, fenchone and norcamphor. Different modulations and amplitudes of the contributing Legendre polynomials are observed despite the similarity in chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
162
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(178 citation statements)
references
References 95 publications
13
162
1
Order By: Relevance
“…2) has shown that for all but the 392 nm 1 eV kinetic energy result the chiral b3 and b5 coefficients are effectively zero, to within close to the statistical uncertainty. This contrasts with studies of camphor, where the magnitude of b3 is comparable to that of b1 8,11 although it parallels observations on MP-PECD of methyl oxirane. 9 Intuitively, b3  0 might appear to suggest no multiphoton character, or at least that the 2-photon intermediate was not aligned, so contributed no additional anisotropy.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…2) has shown that for all but the 392 nm 1 eV kinetic energy result the chiral b3 and b5 coefficients are effectively zero, to within close to the statistical uncertainty. This contrasts with studies of camphor, where the magnitude of b3 is comparable to that of b1 8,11 although it parallels observations on MP-PECD of methyl oxirane. 9 Intuitively, b3  0 might appear to suggest no multiphoton character, or at least that the 2-photon intermediate was not aligned, so contributed no additional anisotropy.…”
Section: Discussioncontrasting
confidence: 96%
“…[1][2][3] Initially developed using synchrotron radiation [4][5][6] , more recently the PECD technique has expanded its reach significantly by utilizing tabletop ultrafast laser-based radiation. [7][8][9][10][11][12][13] It has been shown in the various chiral molecules studied by PECD that a pronounced forward-backward asymmetry in the photoelectron angular distribution can be observed, typically ranging from 1-40% of the total photoionization yield. This PECD asymmetry is two to three orders of magnitude larger than the typical asymmetry observed in (vibrational/electronic) circular dichroism.…”
Section: Introductionmentioning
confidence: 99%
“…Pre--alerted by previous reports 25,37 that similarly sourced commercial fenchone samples may not be enantiopure, and by our own experience with camphor (above), we took additional steps to verify purity of our fenchone samples. The two different enantiomeric samples of fenchone were analyzed by GC×GC--TOFMS to obtain a precise value of the e.e.…”
Section: Fenchone Datamentioning
confidence: 99%
“…CD utilizes the absorption difference of left‐ and right‐circularly polarized light depending on the enantiomer of a chiral molecule (CD effect). It also allows several combinations with other nonenantioselective analysis techniques, such as angular‐resolved photoelectron spectroscopy, nonlinear two‐photon spectroscopy, and mass spectrometry (MS) …”
Section: Introductionmentioning
confidence: 99%